Dialectics of Islamic Law and Positive Law on the 2020–2025 National Divorce Phenomenon and Its Implications for Family Resilience - Ilham Dhiyaul Jabbar; Suryani; Aspandi (UIN Jurai Siwo Lampung, 2026)
Divorce rates in Indonesia experienced significant fluctuations during the 2020–2025 period. BPS data recorded 291,677 cases in 2020, surging sharply to 516,344 cases in 2022 due to the COVID-19 pandemic, before gradually declining to 438,168 cases in 2025, where divorce lawsuits (cerai gugat) heavily dominated at 79%. This latter decline was driven by pre-marital guidance programs and preventive initiatives by the Religious Courts and the Office of Religious Affairs (KUA). This study aims to identify the causal factors of this divorce phenomenon, analyze its impact on family resilience, and examine the normative dialectics between Islamic law and positive law in addressing the trend. Employing a qualitative normative-empirical approach, data were gathered from BPS documents, the Supreme Court annual reports, and in-depth interviews in three epicenter provinces. The findings reveal that the primary triggers are dominated by social factors, particularly continuous disputes (62.28%), post-pandemic financial strains, and social media conflicts. This trend severely undermines family resilience, specifically within the socio-psychological and structural dimensions as outlined in the Minister of PPPA Regulation No. 7 of 2022. Legally, a harmonious dialectic occurs where Islamic jurisprudence and positive law share a substantive consensus regarding the emergency state of divorce, yet both legal systems strongly demand the reinforcement of more responsive, preventive mediation institutions